Indian Guides Pow Wow at YMCA Camp at Sequoia Lake - Watkins, Howard::::::::: (1986)
Members of the Apache Tribe: front left Howard Watkins and Josiah Gordon; Jared Gordon standing and Dean Gordon on far right Distant view showing cabin and ribbons